2020
DOI: 10.1200/jco.19.03077
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Phase II Study of Trastuzumab Beyond Progression in Patients With HER2-Positive Advanced Gastric or Gastroesophageal Junction Cancer: WJOG7112G (T-ACT Study)

Abstract: PURPOSE This study evaluated the continuous use of trastuzumab beyond progression (TBP) in human epidermal growth factor receptor 2 (HER2)-positive advanced gastric or gastroesophageal junction (G/GEJ) cancer. PATIENTS AND METHODS Patients with HER2-positive advanced G/GEJ cancer refractory to first-line chemotherapy with trastuzumab in combination with fluoropyrimidine and platinum were eligible. Patients were randomly assigned to the paclitaxel (80 mg/m2, days 1, 8, and 15, every 4 weeks) or paclitaxel with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
0
32

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(143 citation statements)
references
References 30 publications
7
104
0
32
Order By: Relevance
“…Notably, these groups each remain potential targets not yet routinely implemented for first-line and/or later-line therapy to date, despite numerous studies attempting to do so using classic study designs. (6)(7)(8)(9)(10)(11)14,15,30,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43) An important recent example is the FIGHT study evaluating the anti-FGFR2 antibody, bemarituzumab, for FGFR2 amplified tumors. The study was originally a phase 3 study, but given FGFR2 amplification biomarker incidence of only 5% of GEA and an unclear optimal IHC biomarker cut-off, it was downsized to a phase 2 study in part due to accrual infeasibility for this rare but important genomic subset (https://investor.fiveprime.com/news-releases/news-release-details/five-primetherapeutics-reports-first-quarter-2020-results).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, these groups each remain potential targets not yet routinely implemented for first-line and/or later-line therapy to date, despite numerous studies attempting to do so using classic study designs. (6)(7)(8)(9)(10)(11)14,15,30,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43) An important recent example is the FIGHT study evaluating the anti-FGFR2 antibody, bemarituzumab, for FGFR2 amplified tumors. The study was originally a phase 3 study, but given FGFR2 amplification biomarker incidence of only 5% of GEA and an unclear optimal IHC biomarker cut-off, it was downsized to a phase 2 study in part due to accrual infeasibility for this rare but important genomic subset (https://investor.fiveprime.com/news-releases/news-release-details/five-primetherapeutics-reports-first-quarter-2020-results).…”
Section: Discussionmentioning
confidence: 99%
“…(5) However, numerous targeted and immunotherapies failed in the first and later treatment lines for GEA, including but not limited to anti-HER2 therapy beyond first progression, anti-EGFR, anti-MET, anti-angiogenesis, and anti-PD-1/PD-L1 therapies. (6)(7)(8)(9)(10)(11)(12)(13)(14)(15) A potential contributing explanation for these failed attempts included molecular heterogeneity, (16) not only between patients,(4) but also spatially within patients at baseline, (17) and over time after generation of therapeutic resistance. (18) Novel clinical trial designs attempting to address molecular heterogeneity have been described, (16,19) and are often referred to as basket, umbrella, or expansion-platform studies, the latter since they expand on previous preclinical and clinical evidence supportive of specific biomarker-treatment pairings.…”
Section: Introductionmentioning
confidence: 99%
“…Randomized studies and meta-analyses confirm that active treatment improves OS and QoL compared with BSC alone [ 158 , 175 ]. Currently, second-line treatment options do not differ according to HER2 status—recent trials did not suggest any benefit from trastuzumab beyond progression in HER2-positive gastric cancer treated with trastuzumab in first line [ 176 ]. Among cytotoxic agents, irinotecan, docetaxel, and paclitaxel are all effective agents, supported by randomized trials.…”
Section: Resultsmentioning
confidence: 99%
“…At the point of his disease progression, a biopsy of his liver lesion was taken and an IHC study to reconfirm HER2 status was requested. The rationale of this is based on findings from the T‐ACT trial, which showed that 69% of patients in the study lost HER2 positivity at the point of disease progression on first‐line trastuzumab‐containing therapy 20 . Direct loss of HER2 amplification following trastuzumab‐containing therapy highlights the importance for repeat biopsies to ascertain HER2 status following disease progression and may be the mechanism underlying resistance to anti‐HER2 therapy.…”
Section: Discussionmentioning
confidence: 99%